Design and Analysis of a Spraying Robot - M. Jasim, Fatima; M. Ali, Malik; H. Hamad, Ali (Al-Khwarizmi Engineering Journal, 2022)
An indoor spraying robot is built in this research to solve numerous challenges associated with manual spraying. The mechanical, hardware and essential technologies used are all detailed and designed. The proposed spraying robot’s conceptual design is split into two parts: hardware and software. The mechanical design, manufacturing, electrical, and electronics systems are described in the hardware part, while the control of the robot is described in the software section. This robot’s kinematic and dynamic models were developed using three links that move in the x, y, and z directions. The robot was then designed using SolidWorks software to compute each connection’s deflection and maximum stresses. The characteristics of the stepper motors, power screw and belt drive, are calculated. Finally, an Arduino-Nano controller and stepper motor actuators were used to build and run the robot. As a result, the robot was able to move smoothly vertically and horizontally, according to the findings of the experiments as shown in figures 22, 23, 24, and 25. These figures showed the position and velocity curves of the links of the robot.